Pendampingan Desa Tanjung Lanjut Dalam Pemanfaatan Limbah Organik Melalui Optimalisasi Limbah Rumah Tangga Menuju Desa Wisata Berkelanjutan - Siti Hodijah; Parmadi; Dwi Hastuti; Yulmardi (Studium: Jurnal Pengabdian Kepada Masyarakat, 2022)
One of the objectives of community services in Tanjung Lanjut Village, Muaro Jambi Regency is to assist Tanjung Lanjut Village in the utilization of organic waste through optimizing household waste towards a sustainable tourism village. The number of tourists who visited Tangkas Lake made Tangkas Lake had a lot of garbage which is mostly brought by visitors. In addition, the density of visitors and various activities, both government and village institutions’ activities, had made the village to continue to produce organic and non-organic waste. Therefore, there is a need for empowerment and assistance to the Tangkas Lake community so that waste will not become a problem but a blessing by managing useful waste. Organic waste management by fermentation can be one solution to implement a clean and comfortable environment for the development of Tangkas Lake agrotourism as well as a sustainable tourism village.